Review of Knowledge and Technology Transfer Program in Developing Economies (With case study in Metal Based SMEs in Indonesia) - Fourry Handoko (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2022)
This paper describes the literature review on knowledge and technology program. It concisely articulates: Technology, Knowledge, Technology Transfer, The role of Technology transfer, and SMEs in Indonesia, with particular issue of metal based SMEs in Pasuruan, based of fieldwork research finding. This paper explores technology and technology transfer in general, providing an overall picture regarding these and other related issues. This review shows that many issues relating to technology transfer have been emerging for some decades. However, the review concentrates on the historical chronology of issues that have led to the experience of technology transfer for SMEs in developing countries.